Guinea-Bissau : Second Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2011)
This paper reports on the economic and financial reforms in Guinea-Bissau. After a long period of recession since the beginning of 2000 followed by a slight recovery in 2007, the economy of Guinea-Bissau has entered a new growth spurt in 2008. The budget deficit, which averaged 10 percent of GDP between 2005 and 2007, has been reduced to 3.2 percent in 2008 and 3.0 percent in 2009 by raising more revenue domestically and by controlling expenses.